BOUNDARY CONDITIONS FORMATION OF THE STRESS-STRAIN STATE ANALYSIS OF CITY BUS BODIES - HOLENKO, Kostyantyn; MAKOVKIN, Oleg; POSONSKYI, Sergii (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The presented research proposes a method of forming boundary conditions for the analysis of the Low-floor and Low-entry types of bus body frames under the static load conditions with appropriate measures to optimize the strength during bending and torsion modes of load. The assessment of the stress-strain state of the body frame is performed using the FEM, which is rightfully considered the most effective in the conditions of simulating the real-life behaviour of the metal structures under various load regimes. It is obvious that the main driving force behind the deep integration of FEM into the work process of developing the new bus models are the financial and time constraints of design and production. Besides the existing acute shortage of real tests of completed vehicles using strain gauges is the significant reason of various FEM-based methodologies for passive safety assessment and safety margin determination. From a mathematical point of view, the frame of the bus is a solid body, which in modelling can most strictly be described as a set of geometrically similar elements connected to each other in such a way that they form a structure as close as possible in shape to a real body. Stress-strain state of the bus body frame could be investigated for the different loading modes, but the most popular ones are the bending and torsion regimes, which are typical while the new bus model is designed and obtained. Furthermore, it’s definitely possible to judge, that the guarantee of sufficient safety under the terms of the UN-ECE Regulation (R66, R94, etc) is the height rigidity of the bus body frame during the bending and torsion tests. On the other hand, it is important to understand that the body frame must be equally strong and minimal in terms of material consumption, that’s why our goal is to investigate efficient boundary conditions formation which will provide as close to the natural tests’ behaviour as possible.